2014
DOI: 10.1039/c3ta14913g
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the high-temperature redox chemistry of Sr2Fe1.5Mo0.5O6−δvia in situ neutron diffraction

Abstract: The composition of Sr2Fe1.5Mo0.5O6−δ, a SOFC electrode material, is investigated by neutron diffraction in both highly oxidizing and reducing conditions, and correlated with measured physical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
(40 reference statements)
1
18
0
Order By: Relevance
“…The results showed that the reduced SFM has a slightly larger lattice constant of a = b = c = 3.925 Å than the oxidized SFM ( a = b = c = 3.916 Å), Table . Such fully disordered distribution over the Fe and Mo sites with space group Pm 3̅ m has already reported for SFM structure by several groups, such as Liu and co-workers using powder X-ray diffraction method . However, Muñoz-García suggested an orthorhombic structure with Pnma for SFM based on powder neutron diffraction analysis .…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…The results showed that the reduced SFM has a slightly larger lattice constant of a = b = c = 3.925 Å than the oxidized SFM ( a = b = c = 3.916 Å), Table . Such fully disordered distribution over the Fe and Mo sites with space group Pm 3̅ m has already reported for SFM structure by several groups, such as Liu and co-workers using powder X-ray diffraction method . However, Muñoz-García suggested an orthorhombic structure with Pnma for SFM based on powder neutron diffraction analysis .…”
Section: Resultssupporting
confidence: 53%
“…However, Muñoz-García suggested an orthorhombic structure with Pnma for SFM based on powder neutron diffraction analysis . In addition, a tetragonal I 4/ mcm and a Fe–Mo ordered structure with Fm 3̅ m have been also reported for SFM. , The observed discrepancy between the different research groups could be attributed to the differences in the material preparation conditions …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So, displacements occur in all sublattices, that lead to diffuse scattering. These diffraction effects were also observed by Bugaris and coauthors in their structural investigations of tetragonal phase SrFe 0.75 Mo 0.25 O 3 À δ (3 43 À δ42.75) [11], where they call it "unusual strain broadening". Perhaps, they also deal with the nanodomain state of this phase in a perovskite matrix, that manifested as diffuse scattering.…”
Section: Resultsmentioning
confidence: 60%
“…The "order-disorder" phase transitions in case of nanostructured oxides do not lead to destruction of the materials. At the same time, despite the presence of high-charged cations, which are obstacles to the motion of vacancies, doping has a weak inhibitory effect on oxygen diffusion [9][10][11], and in cases of relatively low substitution degree, for example M ¼Mo 6 þ and y¼ 0.05, even improves the diffusion [9].…”
Section: Introductionmentioning
confidence: 96%